LANGUAGE ACQUISITION IN AUTISTIC CHILDREN - Achmad Basari (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2008)
The term Autism has become popular in Indonesia since the end of 90’s. The suspicious and peculiar cause of autism is stil debatable until today. There are experts who suspect mercury substance of deep water fish to be the main cause of it and some others claim that it is caused by a particular vaccination before a child gets two years old. There are two common symptoms of a child labeled autistic; speech delay and mental retardation. This article describes the ways of an autistic child acquiring his first language in addition to the available theories of language acquisition for children and it also shares the writer’s personal experiences living together with an autistic child of his own.Keywords: Autism, speech delay, mental retardation, languageacquisition, speech therapy